GEP-based method to formulate adhesion strength and hardness of Nb PVD coated on Ti–6Al–7Nb aimed at developing mixed oxide nanotubular arrays. (August 2016) - Rafieerad, A.R.; Bushroa, A.R.; Nasiri-Tabrizi, B.; Fallahpour, A.; Vadivelu, J.; Musa, S.N.; Kaboli, S.H.A.
Abstract: PVD process as a thin film coating method is highly applicable for both metallic and ceramic materials, which is faced with the necessity of choosing the correct parameters to achieve optimal results. In the present study, a GEP-based model for the first time was proposed as a safe and accurate method to predict the adhesion strength and hardness of the Nb PVD coated aimed at growing the mixed oxide nanotubular arrays on Ti67. Here, the training and testing analysis were executed for both adhesion strength and hardness. The optimum parameter combination for the scratch adhesion strength and micro hardness was determined by the maximum mean S / N ratio, which was 350 W, 20 sccm, and a DC bias of 90 V. Results showed that the values calculated in the training and testing in GEP model were very close to the actual experiments designed by Taguchi. The as-sputtered Nb coating with highest adhesion strength and microhardness was electrochemically anodized at 20 V for 4 h. From the FESEM images and EDS results of the annealed sample, a thick layer of bone-like apatite was formed on the sample surface after soaking in SBF for 10 days, which can be connected to the development of a highly ordered nanotube arrays. This novel approach provides an outline for the future design of nanostructured coatings for a wide range of applications. Graphical abstract: Highlights: A GEP model was developed to formulate adhesion strength and hardness of Nb PVD coated on Ti67. Values in the training and testing were very close to the actual experiments designed by Taguchi. A homogenous and high-purity structure was achieved after annealing at 440 °C for 30 min. A bone-like apatite layer was formed after soaking in SBF for 10 days.